Biomechanics of Rugby Tackle Techniques in Youth and Adult Players: A Systematic Review of Age-Specific Injury Risk and Performance Implications - Henry C. A. Edgington; Bernard X. W. Liew; Sharief. Hendricks; Benjamin Jones; Behnam Gholami; Matthew Barrett; Abishek Gurung; Jason Moran (Sports Medicine, 2026)
Abstract Background Tackling is a vital skill in rugby that greatly influences both performance outcomes, such as carry distance and possession gain, and injury risk, such as the frequency of concussions and cervical injuries. Approximately 72% of head impacts in rugby occur during tackles, leading to concussions and cervical trauma. Technical skill in tackle mechanics is therefore central to player safety. Objectives This systematic review evaluates tackle biomechanics across age groups to identify differences in technique and injury patterns and to inform age-specific coaching strategies. Methods This systematic review was registered with PROSPERO (ID CRD420251103973) and adhered to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020 guidelines. PubMed, SPORTDiscus, Web of Science, ScienceDirect and Google Scholar were searched without date restrictions. Studies analysing tackle biomechanics, injury mechanisms or performance outcomes in youth or adult rugby players were eligible. Two reviewers independently screened titles, abstracts and full texts. Risk of bias was assessed using the Downs and Black checklist. Thirty-two studies met the inclusion criteria. Results Across the 32 included studies, three patterns emerged. First, tackler head-in-front positioning was associated with a five- to eight-fold increase in per-tackle concussion risk and was more common in youth players than adults. Second, dominant-shoulder tackles consistently produced lower head accelerations than non-dominant tackles, with this safety advantage eroding under match-induced fatigue. Third, youth players showed lower tackle proficiency scores than adults, characterised by reduced hip and knee flexion, less leg drive and more frequent arm-only contact. Across studies, evidence quality was moderate; few studies used non-injury controls to support causal claims. Conclusions Age-specific coaching strategies are warranted to optimise tackle safety and performance. Emphasising correct head positioning, dominant-shoulder engagement and lower-limb mechanics may mitigate injury risk in youth rugby. The current evidence base supports associations rather than firm causal claims; future case–control studies that compare injury and non-injury tackles within the same match environment would strengthen this evidence.